Comprehensive analysis of metabolomics on flesh quality of yellow catfish (Pelteobagrus fulvidraco) fed plant-based protein diet - Li, Xue; Wang, Shidong; Zhang, Muzi; Jiang, Haibo; Qian, Yunxia; Wang, Rixin; Li, Ming (Frontiers in Nutrition, 2023)
Background To investigate the mechanism of plant protein components on nutritional value, growth performance, flesh quality, flavor, and proliferation of myocytes of yellow catfish (Pelteobagrus fulvidraco). Methods A total of 540 yellow catfish were randomly allotted into six experimental groups with three replicates and fed six different diets for 8 weeks. Results and Conclusions The replacement of fish meal with cottonseed meal (CM), sesame meal (SEM), and corn gluten meal (CGM) in the diet significantly reduced growth performance, crude protein, and crude lipid, but the flesh texture (hardness and chewiness) was observably increased. Moreover, the flavor-related amino acid (glutamic acid, glycine, and proline) contents in the CM, SEM, and CGM groups of yellow catfish muscle were significantly increased compared with the fish meal group. The results of metabolomics showed that soybean meal (SBM), peanut meal (PM), CM, SEM, and CGM mainly regulated muscle protein biosynthesis by the variations in the content of vitamin B6, proline, glutamic acid, phenylalanine, and tyrosine in muscle, respectively. In addition, Pearson correlation analysis suggested that the increased glutamic acid content and the decreased tyrosine content were significantly correlated with the inhibition of myocyte proliferation genes. This study provides necessary insights into the mechanism of plant proteins on the dynamic changes of muscle protein, flesh quality, and myocyte proliferation in yellow catfish.